Slovenska literarna zgodovina danes - Hladnik, Miran (Slavistična revija, 2013)
The article urges abandoning the outdated concept of a synthetic national "grand narrative" of literature and replacing it with a listing concept. The motivation for changing the literary historical paradigm derives from a) the sharp increase in the number of publications, which are no longer manageable in the traditional manner, b) public Internet access to large bibliographic and text collections and tools for manipulating them, c) the practice publishing encyclopedic literary scholarship in Wikipedia, d) cognizance of apprehension of the world as a list. The opportunity exists for a literary history composed as a mosaic or mycelia in the framework of Wikipedia's sister pages Wikibooks, Wikisource, and Wikiversity, which motivate students' and other interested humanists' participation in literary studies. There are ample qualified experts. The change is fitting for the information society, which is based on distributed cooperative, networked knowledge production and the end of the exclusivity of aesthetic selection.
Keywords: 21.st.; 21st century; informacijska družba; internet; internet encyclopedias; literary progress; razvoj; Slovene literary history; Slovene literature; slovenska književnost; slovenska literarna zgodovina; spletne enciklopedije